Photocatalytic Water‐Splitting by Organic Conjugated Polymers: Opportunities and Challenges. Issue 7 (8th March 2022) - Mansha, Muhammad; Ahmad, Tauqir; Ullah, Nisar; Akram Khan, Safyan; Ashraf, Muhammad; Ali, Shahid; Tan, Bein; Khan, Ibrahim
Abstract: The future challenges associated with the shortage of fossil fuels and their current environmental impacts intrigued the researchers to look for alternative ways of generating green energy. Solar‐driven water splitting into oxygen and hydrogen is one of those advanced strategies. Researchers have studied various semiconductor materials to achieve potential results. However, it encountered multiple challenges such as high cost, low photostability and efficiency, and required multistep modifications. The conjugated polymers (CPs ) have emerged as promising alternatives for conventional inorganic semiconductors. The CPs offer low cost, sufficient light absorption efficiency, excellent photo and chemical stability, and molecular optoelectronic tunable characteristics. Furthermore, organic CPs also present higher flexibility to tune the basic framework of the backbone of the polymers, amendments in the sidechain to incorporate desired functionalities, and much‐needed porosity to serve better for photocatalytic applications. This review article summarizes the recent advancements made in visible‐light‐driven water splitting covering the aspects of synthetic strategies and experimental parameters employed for water splitting reactions with special emphasis on conjugated polymers such as linear CPs, planarized CPs, graphitic carbon nitride (g‐C3 N4 ), conjugated microporous polymers (CMPs ), covalent organic frameworks (COFs ), and conjugated polymer‐based nanocomposites (CPNCs ). The current challenges and future prospects have also been described briefly. Abstract : This review article summarizes the recent advancements made in visible‐light‐driven water splitting covering the aspects of synthetic strategies and experimental parameters employed for water splitting reactions with special emphasis on conjugated polymers such as linear CPs, planarized CPs, graphitic carbon nitride (g‐C3 N4 ), conjugated microporous polymers (CMPs ), covalent organic frameworks (COFs ), and conjugated polymer‐based nanocomposites (CPNCs ).